2021
DOI: 10.1017/s0022377821000751
|View full text |Cite|
|
Sign up to set email alerts
|

Linear dispersion relation of geodesic acoustic modes driven by trapped and circulating energetic particles

Abstract: We derive the local dispersion relation of energetic-particle-induced geodesic acoustic modes (EGAMs) for both trapped and circulating ion beams with single pitch angle slowing-down and Maxwellian distributions, as well as a bump-on-tail distribution in tokamak plasmas. For slowing-down and Maxwellian particles, the solutions of the local dispersion relation give the spectrum, growth rate and thresholds of excitation as functions of the pitch angle, beam density and frequency of the energetic particles bounce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Whereas, positive gradients of the distribution functions in velocity space are needed to drive EGAMs, and as a consequence of which a certain portion of EPs will be redistributed to lower energies [28]. In previous work, analytical anisotropic distribution functions are bump-on-tail [10,11,28] and slowing down with pitch dependency [8,10,13,22], as well as single pitch Maxwellian [10]. Analytical theory and simulations adopting pitch dependent slowing down distribution function described it as function of Λ = μB/E, with μ being the magnetic moment of the particle, E total kinetic energy and B background magnetic field.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Whereas, positive gradients of the distribution functions in velocity space are needed to drive EGAMs, and as a consequence of which a certain portion of EPs will be redistributed to lower energies [28]. In previous work, analytical anisotropic distribution functions are bump-on-tail [10,11,28] and slowing down with pitch dependency [8,10,13,22], as well as single pitch Maxwellian [10]. Analytical theory and simulations adopting pitch dependent slowing down distribution function described it as function of Λ = μB/E, with μ being the magnetic moment of the particle, E total kinetic energy and B background magnetic field.…”
Section: Introductionmentioning
confidence: 96%
“…EP density is one of the main parameters affecting it. Simulations and analytical computations showed that an increase in EP concentration leads to an increase of growth rate of the mode, marking at a certain value of EP fraction with respect to electron density n EP /n e the threshold value for the transition from a damped to an excited mode [8][9][10][20][21][22][23]. On the other hand, the frequency is usually found to be decreasing because of the transition from an higher frequency GAM to a lower frequency EGAM for increasing EP fraction.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations